Understanding Patients' Knowledge of Risk Behavior in Managing Emotional Control - Santoso, Dona Yanuar Agus; PH, Livana (Indonesian Journal of Global Health Research, 2023)
Mental health remains an ongoing concern within both global and national contexts, with schizophrenia standing out as a significant manifestation marked by a spectrum of symptoms, including both positive and negative behavioral manifestations, such as violent tendencies. The propensity towards violent behavior signifies a facet of anger expression, often demonstrated through threats, self-inflicted harm, or harm towards others. This study endeavors to evaluate the emotional regulation capabilities of patients affected by this condition. Employing a descriptive research design, the study sample comprises 20 participants selected through purposive sampling methods. Data collection procedures encompassed observational techniques alongside structured interviews. Analysis of the gathered data employed univariate techniques, particularly through frequency distribution analysis. The findings underscore a prevalent tendency among patients to employ techniques such as deep breathing and physical engagement with pillows or mattresses as mechanisms for emotion regulation.